Organological Study of Canang Kayu in Aceh Singkil - Purba, Junaidi; Purba, Mauly; Lubis, Tasnim (Talenta Publisher, 2024)
This study aimed to describe the organological aspects of making and playing the Canang kayu (wooden canang) instrument. Canang kayu is one of the local musical instruments from Aceh Singkil Regency. It is included as a percussion instrument and classified as an idiophone (a solid musical instrument whose sound comes from the instrument itself). This musical instrument is a form of xylophone (a percussion instrument consisting of a series of wooden blocks placed horizontally and struck with a unique beater). A qualitative method was applied in this study. Data were collected through observation participation, literature studies, and interviews with the Canang kayu makers, Canang kayu players, and staff in Majelis Adat Aceh Singkil (Aceh Singkil Traditional Council). The data source was pictures of Canang kayu and interview recordings with informants. The result of the study showed that the primary raw materials for canning kayu are bamboo and tree wood/Terentang putih tree (local people also call it cupping wood). Terentang putih tree (Campnosperma auriculatum) is a type of tree that grows in swamps. This tree can be found near Aceh Singkil forest. It is pretty difficult to find at present. The material for making Canang kayu should consider the size, tool used, raw material, and the making process. For playing technique, Canang kayu can be played by placing it on feet or a container. The Canang kayu instrument has a strong relationship with maintaining its material and local knowledge of making concepts that seize the cultural values of the Aceh Singkil people. It can be concluded that the making and playing technique is an effort to preserve one of Aceh Singkil's cultural heritages toward the identity and important insights in enriching knowledge about Canang kayu as an Aceh Singkil traditional art.